Factors Influencing Individual Tax Compliance in Surabaya - Adhityawati Kusumawardhani; William Limanto; Fernando Billy Sugiarto (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2026)
Under Indonesia’s self-assessment tax system, individual taxpayers are entrusted with primary responsibility for determining and fulfilling their tax obligations, making voluntary compliance a critical issue in tax administration. This study investigates the extent to which tax knowledge and tax awareness shape individual taxpayer compliance in Surabaya. Drawing on survey data collected from 202 registered individual taxpayers (NPWP holders), the analysis employs multiple linear regression to examine the proposed relationships. The findings demonstrate that tax knowledge plays a significant role in enhancing compliance by improving taxpayers’ capacity to understand tax regulations and procedural requirements. In addition, tax awareness is found to exert a positive influence on compliance, indicating that internalized responsibility and personal commitment to tax obligations are central to compliant behavior. Taken together, these results suggest that individual tax compliance in Surabaya is driven more strongly by internal motivation than by reliance on enforcement mechanisms. By emphasizing the psychological and behavioral foundations of compliance, this study contributes to the growing literature on voluntary tax compliance and offers practical implications for tax authorities, particularly the importance of education and awareness-oriented strategies in fostering sustainable taxpayer compliance.